Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Manco Fernández, Alvaro Raúl (2018)
This case report aims to evaluate the proposal of a strategic plan for the entry into the Peruvian market of the Japanese company Fast Retailing Group under the UNIQLO brand. With more than 20 years of experience in the global market, the Japanese company is characterized by the development of accessible garments with the highest quality that can be found in the Fast Fashion market. The analysis concentrates on this industry which is relatively new within Peru. However, it concentrates a great potential for growth as evidenced by companies such as Zara, Forever 21, H&M, etc., which through various strategies they have implemented have achieved the goal of conquering the public and turning fashion into a consumed good for the masses. For the first instance, it is necessary to analyze and determine the current situation in which Fast Retailing finds itself. An internal analysis will determine whether the business model used by the group, in addition to its strengths and weaknesses, is a solid competitive advantage that will allow them to take advantage of the opportunities and combat the threats of the new geographic market they are entering. Once the overall picture is understood, appropriate strategies will be developed and sustained to ensure success while maintaining a focus on differentiation. Medium- and long-term objectives will also be set and it will be determined whether the identified business units will need to be restructured. Finally, the control mechanisms to ensure the achievement of the objectives will be determined and the conclusions and recommendations reached after the extensive analysis of the opportunity will be presented.